مظاهر التغير القيمي في المدينة الحديثة - قب, شهناز; حمزاوي, سهى (Sciences de l'Homme et de la Société, 2017)
يهدف هذا البحث إلى معرفة موضوع القيم و أهميته بالنسبة للفرد و المجتمع باعتباره نسق اجتماعي أو تنظيم عضوي يحكم حياتنا الاجتماعية يتعرض إلى عملية التغير في ظل عوامل اقتصادية و اجتماعية و ثقافية و سياسية مختلفة يتأثر بها و يؤثر في مدى استمراريتها ،،و خاصة على مستوى المدينة الحديثة أين يزداد الأمر تعقيدا لما فيها من انساق اجتماعية مختلفة تتكامل فيما بينها مشكلة بذلك الوحدة في المبادئ والأفكار و المعتقدات ،لهذا فقد تم  الكشف عن آفاق التغير القيمي في المدينة الحديثة و أهم المظاهر التي تنتج عنها إضافة إلى  ماتؤول إليه في المستقبل حيث  خلص البحث إلى فكرة أساسية مفادها إن التغير القيمي هو ظاهرة حتمية تتعرض لها كل المجتمعات و خاصة الحضرية منها بسبب مواكبة التحضر بجميع مظاهر التقدم و العصرنة،  و ما تفرضه العولمة من قيم جديدة ،  يصبح لزاما على افرد المجتمع إتباع أنماط معينة من السلوك و إقامة علاقات اجتماعية أكثر تعقيدا، و اختلافا عما اعتادوا عليه في الماضي.   Abstract : This research aims to know the values and importance of the values to the individual and society as a social or social range or a social organization that governs our social life and it is subjected to the process of change under different economic, social, cultural and political factors.This social range is influenced by these factors and it affects the extent of its continuity, especially at the level of the modern city where it is becoming modern city where it is becoming more complex because of the different social patterns integrated among them to construct the unity of principles and ideas and beliefs therefore, the prospects of value change in the modern city have been revealed as well as the most important aspects that result in it in the future.The research concluded to a main idea that is the value change is an inevitable phenomenon for all societies, especially urban ones, due to the urbanization of all aspects of progress and modernization, and to the imposition of new values imposed by globalization, it becomes imperative for individual to follow certain patterns of behavior and to establish more complex social relations, and different from what they used to in the past.